THE ROAD TO THE SIGNING OF THE AGREEMENT OF THE CENTURY - IBRAHIMOVA AYSEL ARZU GIZI (Scientific Research and Experimental Development, 2024)
After Azerbaijan gained independence, the main goal was to introduce Azerbaijan to the world. One of the things done to realize this was the entry of foreign investors into Azerbaijan and the implementation of capital flow to certain areas of the economy. Shortly after coming to power, the great leader Heydar Aliyev implemented a world-wide policy called the Contract of the Century. With this, Azerbaijan began to be recognized by world countries for its development rate. After the dissolution of the Soviet Union in 1991 and Azerbaijan's declaration of independence, the country decided to attract Western investments to implement projects related to the development of its oil reserves. Meanwhile, international companies had shown interest in the oil fields discovered in the Azerbaijani sector of the Caspian Sea in the 1980s. These companies initially focused on the oil reserves of the "Chirag" and "Azari" fields. In January 1991, the Azerbaijani government began to announce tenders for the development of these projects. BP, Statoil, Amoco, Unocal, and other companies joined the project. In 1991, Amoco, BP, McDermott, Pennzoil, Ramco, Unocal, TPAO, and a group of other foreign companies, including Statoil, initiated negotiations with Azerbaijan regarding the improvement of the "Chirag" and "Gunashli" fields in the Azerbaijani sector of the Caspian Sea, with a planned duration of three years. Negotiations continued throughout this period regarding joint production of large oil fields【1. pp. 9-10】.